2000
DOI: 10.1111/j.1349-7006.2000.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Intestinal Mucosal Immunity in Tumor‐bearing Mice by Lactoferrin

Abstract: We have previously demonstrated that oral administration of bovine lactoferrin (bLF) markedly increases CD4 + and CD8 + T cells and NK (asialoGM1 + ) cells in the blood of tumor-bearing mice and enhances anti-metastatic activity. In this paper, we document that oral administration of bLF and bLF-hydrolysate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 18 publications
3
75
1
Order By: Relevance
“…A previous report indicated that IFN-ª production by CD4 þ splenocytes in mice is increased by oral administration of LF [30]. LF feeding also increased the number of IFN-ª þ cells in the small intestinal mucosa of mice [31]. These findings suggest the possibility that the macrophage-activating component released from the guinea-pig MNC is an IFN-ª-like cytokine.…”
Section: Discussionmentioning
confidence: 48%
“…A previous report indicated that IFN-ª production by CD4 þ splenocytes in mice is increased by oral administration of LF [30]. LF feeding also increased the number of IFN-ª þ cells in the small intestinal mucosa of mice [31]. These findings suggest the possibility that the macrophage-activating component released from the guinea-pig MNC is an IFN-ª-like cytokine.…”
Section: Discussionmentioning
confidence: 48%
“…A similar effect in spleen from adult mice fed with colostrum has been described 14 . An increase in the NK cell proportion after lactoferrin administration has been found in circulating cells in adult rats 15 and in intestinal cells in mice 16 . Moreover, our data derived from the end of suckling (day 21) suggested that NKR-P1Aþ LPL from WPC supplemented animals exhibited a more mature intestinal phenotype (NKR-P1Aþ CD8-), which corresponds to that found in adult age, than reference animals did.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bLF may be applicable for inhibition of carcinogenesis by other heterocyclic amines with similar activation processes by CYP1A2. However, as administration of 2% bLF alone slightly, but significantly, reduced DEN/ PH-induced liver carcinogenesis (Table II), the observed up-regulation of immune reactions in the intestine with stimulation of cytotoxic T cells and induction of interleukin-18 in mice, 41) may also play a role. Further studies are required to clarify this point.…”
Section: Discussionmentioning
confidence: 99%